ANALYZING THE SOCIO-POLITICAL DYNAMICS AND CURRICULUM CHALLENGES IN INDONESIAN ISLAMIC SCHOOLS: A COMPREHENSIVE STUDY ON EDUCATION MANAGEMENT FOR SUSTAINABLE DEVELOPMENT - Miranu Triantoro; Halimatussa'diyah; Ekbal Santoso; Udin Erawanto; Diah Afrianti Rahayu (Adisam Publisher, 2023)
In our comprehensive study,